Comparison of Methods for Coccidioidomycosis Complement Fixation - Huppert, Milton (1970)
A Laboratory Branch Task Force of the National Communicable Disease Center has proposed a standardized complement fixation procedure (LBCF) and an adaptation of this to microtitration techniques (MT) as uniform methods for performing complement fixation (CF) tests. A common procedure should make CF results from one laboratory more comparable to another. In addition, it would be preferable if the common procedure reproduced the titer levels of a testing procedure which is to be replaced, particularly when valid clinical interpretations have been derived from the latter. Replicated sets of sera were tested by the LBCF, MT, and the standard Smith CF procedure for coccidioidomycosis. Results with all three procedures were highly reproducible within an acceptable one-tube variation of a twofold dilution series, but the frequency of one-tube variations was greater with the MT method than with the other two. There was no statistical difference in the titers obtained with the Smith and LBCF procedures, but there was a significant difference when the MT results were compared to those with the Smith method. The LBCF method should be acceptable as a standardized and uniform CF procedure for coccidioidomycosis, subject to comparative testing between different laboratories.